A GIS framework for the application of the land degradation neutrality concept in Mediterranean landscapes. Issue 25 (13th December 2022) - Al Sayah, Mario J.; Abdallah, Chadi; Khouri, Michel; Nedjai, Rachid; Darwish, Talal; Khatib, Houssein
Abstract: Given the absence of soil loss indicators within the Land Degradation Neutrality (LDN) framework, this study integrates land cover suitability, soil erosion and sediment transport as complementary Mediterranean-tailored indicators. The 309 km 2 Lebanese Nahr Ibrahim basin was chosen for this purpose. Land cover suitability was determined by combining land capability-land cover maps, while soil erosion and sediment transport were assessed using the CORINE and SWAT models, respectively. Under current conditions, the following was found: a 34.84% land cover suitability; 4% low, 39.55% moderate and 56.45% high soil erosion risks zones, and 2.85% low, 26% moderate and 68.15% high sediment yields zones. Through the LDN response strategy based land use plan, land cover suitability increased by 26.54%, while soil erosion risks changed by: +3.1% low, +10.85% moderate and −18% high risk zones. For sediment transport, changes were: 0% low, +10.85% moderate and −18% high risk zones, hence the multi-effectiveness of LDN.